Pengolahan Limbah Cair Rumah Tangga Menggunakan Tanaman Bambu Air (Equisetum Hyemale) - Fitria Wulandari; Eko Hartini (Dian Nuswantoro Semarang, 2016)
Detergent have been used widely both in domestic and industry because it was more effective than others cleaner agents. Unfortunately it cause the water pollution that dangerous for environment. The water bamboo plant can reduce waste water pollution. This research aims to analyze effectiveness in reducing the domestic waste water by the water bamboo plants. This was experiment research conducted in a laboratory scale. There was one treatment with three repetition and three times measurements.The result of laboratory analysis showed that bamboo plants that mixed with the artificial wetland system, decrease residual detergent in wastewater until 99,91 % in the six days.Â The advantages of domestic wastewater treatment with this method produced good water quality accordance with wastewater standard generated from domestic activities and also can be used for watering plants.Keywords: domestic waste water, bamboo water plants